Italian National Recovery and Resilience Plan: a Healthcare Renaissance after the COVID-19 crisis? Recovery and Resilience beyond COVID-19 - Filippini, Tommaso; Vinceti, Silvio Roberto (Acta Biomedica Atenei Parmensis, 2021)
Proposed for the first time by European Commission in May 2020, the “NextGenerationEU” (NGEU) program is the European Union’s most important effort to address key issues relating to public health and healthcare, digital and technological innovation, climate change, sustainable mobility, and key sociocultural aspects. In addition, the NGEU represents a response to the COVID-19 crisis through an extremely powerful financial intervention (over 800 billion euros). Italy is one of the main recipients of the NGEU plan’s resources with almost 200 billion euros received in grants and loans. Implementation of the NGEU in Italy will take place through the National Recovery and Resilience Plan (NRRP). The NRRP not only describes how the NGEU resources will be used, but it singles out crucial public law reforms in national legislation and organization. Unsurprisingly, public health intervention represents a major component of the NRRP. Here we summarize and discuss the rules, regulations and perspective envisaged by the NRRP to foster effective healthcare and to reshape the Italian National Health System through the redesigning of primary care, enhanced communication between hospital and community healthcare, and stronger implementation of digital technologies in public health. (www.actabiomedica.it)